2006
DOI: 10.1111/j.1365-2230.2006.02148.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 is significantly elevated in plasma of patients with vitiligo treated with psoralen plus ultraviolet A1

Abstract: Systemic PUVA therapy in vitiligo may have a generalized mitogenic effect on melanocytes through the release of ET-1 into the circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In vitiligo, a significantly lower expression of GM‐CSF, SCF, and bFGF have been found compared with partially affected or unaffected skin (Moretti et al., 2002). UVR increases the number of residual melanocytes most probably by enhancing melanocyte growth factors such as bFGF and endothelin‐1 (ET‐1) (Abdel‐Naser et al., 2006; Hirobe, 2005) . The activation of stem cells in the hair follicle and interfollicular epidermis, ‐which could escape the immune destruction mechanisms since they do not express melanocyte differentiation markers‐, could provide differentiated melanocytes for repigmentation (Osawa et al., 2005).…”
Section: Medical Therapymentioning
confidence: 99%
“…In vitiligo, a significantly lower expression of GM‐CSF, SCF, and bFGF have been found compared with partially affected or unaffected skin (Moretti et al., 2002). UVR increases the number of residual melanocytes most probably by enhancing melanocyte growth factors such as bFGF and endothelin‐1 (ET‐1) (Abdel‐Naser et al., 2006; Hirobe, 2005) . The activation of stem cells in the hair follicle and interfollicular epidermis, ‐which could escape the immune destruction mechanisms since they do not express melanocyte differentiation markers‐, could provide differentiated melanocytes for repigmentation (Osawa et al., 2005).…”
Section: Medical Therapymentioning
confidence: 99%
“…The clinical efficacy of NB‐UVB is partially due to its immunomodulating effects, which halt melanocytes' destruction, and so stop depigmentation. Yet, the main mechanism of its action is enhancing the process of repigmentation by stimulating melanocytes differentiation, migration and proliferation most probably by enhancing melanocyte growth factors such as basic fibroblast growth factor (bFGF) and endothelin‐1 (EN‐1) 17 . Indeed, Awad 18 previously demonstrated that NB‐UVB in vitiligo skin induces proliferation and migration of amelanotic spindle cells, as melanocyte precursors, to repopulate the epidermis with new generations of melanocytes restoring the pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Furthermore, EDN1 was found to be increased in patients undergoing PUVA treatment indicating a role of this peptide in vitiligo pathogenesis. [ 19 ] Besides, EDN1 is a strong vasoconstrictive agent which may contribute to controlling the inflammatory process seen in vitiligo. Indeed, blocking the EDN1/EDNRA signaling resulted in the loss of pigmentation in vivo .…”
Section: Discussionmentioning
confidence: 99%